Dual inhibition of mTOR and calcineurin pathways mitigates missing self–induced NK cell–mediated microvascular rejection - Sarah Hamada; Jack Beadle; Alice Koenig; Basile Sugranes; John Ferdinand; Chien-Chia Chen; Virginie Mathias; Maeva Eloudzeri; Thomas Barba; Helena Paidassi; Carole Saison; Valérie Dubois; et al. (Proceedings of the National Academy of Sciences, 2026)
The inability of graft endothelial cells to deliver HLA-I-dependent inhibitory signals to recipient natural killer (NK) cells (missing self, MS), drives donor-specific antibody-independent microvascular inflammation (MVI), leading to graft failure. This study aimed to elucidate the signaling pathways involved in MS-associated NK cell activation and explore therapeutic strategies. Analyses of kidney graft biopsies identified calcium signaling pathways and mTOR as a key regulator of MS-induced NK cell activation. Two experimental models were developed to mimic the pathological condition: in vitro cocultures of human NK cells with allogeneic microvascular endothelial cells and a murine heart transplantation model. These models showed that while calcineurin inhibitor (CNI) alone had a limited impact, combining CNI with mTOR inhibitors (mTORinh) synergistically reduced NK cell activation and endothelial damage. In a pilot clinical study involving 50 renal transplant recipients with MS-associated NK cell–mediated microvascular inflammation, patients who tolerated mTORinh introduced on top of CNI at diagnosis demonstrated reduced MVI lesions and improved graft survival compared to a historical cohort left on CNI and mycophenolate mofetil. This translational study identifies mTOR inhibition as a pivotal adjunct to CNI in mitigating MS-associated NK cell–mediated inflammation, potentially improving long-term graft outcomes.